Filosofai, poetai ir raganos = Philosophers, poets, and witches - Razauskas, Dainius (Religija ir kultūra, 2013)
There are some metaphors used already in many ancient traditions on the ground of which the concepts of philosopher, poet, and witch, or wizard, can be compared. Two of them are shortly dicussed here. The first is the metaphor of "seeing’: ancient Greek philosophers, as also ancient Indian sages, speak of their occupation as consisting in the capacity of mental sight; poets from earliest times call themselves seers; many nouns for witch and wizard in different languages derive from the verbs meaning ‘to see’. The second metaphor discussed here is ‘flying’: ancient Greek philosophers, as also ancient Indian seers, speak of their mental flights; poets do fly and confess of having wings from the times immemorial until nowadays; and some of Lithuanian witches were accused of having flown and the bird’s feathers found in their hairs were considered as an evidence for that (not to speak of the well-known feathers in the garment of Siberian shamans, American Indian cheafs and wizards, etc.). It seems, then, that philosophers, poets and witches, or wizards, represent one and the same mental, religious, and cultural phenomenon the different conception and interpretation of which depends primarily on the conscious awareness of a methaphor.